No ordinary assignment ebook A memoir. - Ferguson, Jane (2023)
"A haunting memoir of disarming honesty. . . a remarkable testament to the anguish and the beauty of foreign correspondence."—Roger Cohen, New York Times Paris bureau chief and author of An Affirming Flame From award-winning journalist Jane Ferguson, an unflinching memoir of ambition and war—from The Troubles to the fall of Kabul. Jane Ferguson has covered nearly every war front and humanitarian crisis of our time. She reported from Yemen as protests grew into the Arab Spring; she secured rare access to rebel-held Syria, where foreign journalists were banned, to cover its civil war. When the Taliban claimed Kabul in 2021, she was one of the last Western journalists to remain at the airport as thousands of Afghans, including some of her colleagues, struggled to evacuate. Living with sectarian violence was nothing new to Ferguson. As a child in Northern Ireland in the 1980s and '90s, The Troubles meant bomb threats and military checkpoints on the way to school were commonplace. Books by Dervla Murphy and Martha Gellhorn offered solace from her turbulent family, and an opportunity to study Arabic in Yemen came as a relief—and a ticket to the life in journalism she imagined. Without family wealth or connections, she began as a scrappy one-woman reporting team, a borrowed camera often her only equipment. Networks told her she had the wrong accent, the wrong appearance, not enough "bang-bang shoot-'em-up." Still, Ferguson threw herself into harm's way time and again, determined to give voice to civilian experiences of war. In the face of grave violence and suffering, this seemed a small act of justice, no matter the risks. Ferguson's bold debut chronicles her unlikely journey from bright, inquisitive child to intrepid war correspondent. With an open-hearted humanity we rarely see in conflict stories, No Ordinary Assignment shows what it means to build an authentic career against the odds.